THE INFLUENCE OF THE LEARNING CONTEXT ON ESL LEARNERS’ USE OF COMMUNICATION STRATEGIES: A CASE STUDY - Nguyen, Thu Hien (2021)
This study investigates the effect of the context of learning—―at home‖ (AH) classroom versus study abroad (SA) on 12 types of communication strategies (CSs) used by learners of learners of English as a second language. Data collected from the two subjects discern their choice of CSs and the effects of external factors on the difference. The findings express a significant effect of context on CSs use: Student in the SA context used fewer CSs than their classroom counterparts, and SA learner tends to use function-oriented strategies but AH subject relies more on reduction and avoidance techniques